LEARNING INTERACTION IN WEB BASED LEARNING IN SPEAKING II CLASS OF ENGLISH EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF BANDAR LAMPUNG UNIVERSITY - Upeka Mendis; Arnes Yuli Vandika (Bandar Lampung University (UBL), 2016)
As we know that technology is the most important need for people nowadays. Without technology even we cannot think that we can complete our all works, so technology takes very important place in globalization area. Due to development of technology most of people use it as a tool for the leaning in the classroom or outside of the classroom. Example: - e-learning, distance learning, blended learning and etc. technological tools are very easy and cheaper than traditional methods. These learning styles can use as effective method for teaching and learning. By using technological tools in the classroom students can get many information and they can explore their ideas with others. Most of teachers in nowadays really want to change their styles of teachings. Web based learning is the most common use for the teaching and learning, but we must know about learners interaction. How learners interact with we based learning environment. Indeed it has been said learning is impossible without meaningful interaction. However, this kind of interaction does not occur by itself. The primary goal of this paper is to know how students interact with online learning.